DIVERSITY OF BAMBOOS AROUND SPRINGS IN MALANG EAST JAVA - Solikin Solikin (The East Java Biological Society, 2013)
Bamboos have important roles to people in the villages area. They are planted and used by the people for making houses, food, buckets, fences, ropes, fuels, musical instruments and plaits. The root distribution of Bamboos is large and fibrous, also the growth of their new clumps is ascendant so the Bamboos has good potency for water and soil conservation on river banks, around the springs, hillsides and scarps. The survey to invent the bamboos growing around the springs was conducted in Singosari, Lawang, Karangploso, Dau and Lowokwaru Malang East Java in May 2009. The Bamboos invented at 0-100 m from the springs. The results Showed that there were four Bamboos founded around the springs namely Bambusa blumeana,Dendrocalamus asper, Gigantochloa atter and Gigantochloa apus. Dendrocalamus asper was the most dominant species founded around the springs with relative frequency, relative density and important value index is 45.83 ; 58.49 and 104.32 respectively.